Water-based environment-friendly coating and local printing transfer paper thereof
By using propylene glycol methyl ether acetate-water azeotropic drying aid and fluorocarbon surfactant, combined with infrared pre-baking and gradient hot air drying technology, the problems of slow drying speed and pinholes in water-based coatings have been solved, achieving rapid drying and high-precision printing to meet industrial needs.
Patent Information
- Application Number
- CN202511943384.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-01-27
AI Technical Summary
Traditional water-based environmentally friendly coatings have a slow drying speed, are prone to forming pinholes, and cannot meet the needs of high-speed printing and instant transfer. Furthermore, their rheological control is complex, affecting the adhesion of the coating and the printing accuracy.
The coating formulation and process are optimized by using a synergistic effect of propylene glycol methyl ether acetate-water azeotropic fast-drying agent and fluorocarbon surfactant, combined with 50℃ infrared pre-baking and 110℃ gradient hot air drying, along with 30kHz ultrasonic treatment of gas-phase nano α-Al2O3 and self-crosslinking polyether thickener, and precise coating with laser-engraved gravure rollers and infrared laser non-contact scanning.
It achieves rapid drying of the coating, no pinholes, clear edges, meets micron-level local printing precision, has low VOC residue, improves production efficiency, and is environmentally friendly.
Smart Images

Figure CN121407421A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water-based environmentally friendly coatings technology, and specifically to a water-based environmentally friendly coating and its local printing transfer paper. Background Technology
[0002] In traditional printing and coating processes, water-based environmentally friendly coatings are favored due to their low volatile organic compound emissions. However, their drying speed is significantly slower than that of solvent-based coatings, becoming a major bottleneck restricting their efficient application. Because water has a high latent heat of vaporization, traditional water-based coatings require a long surface drying time under normal temperature or conventional hot air drying conditions, often tens of seconds or even longer. This not only reduces production efficiency but also easily leads to adhesion or deformation of the coating before it is fully dried, making it difficult to meet the industrial demands of high-speed printing and instant transfer.
[0003] Furthermore, water has a high surface tension, which easily leads to defects such as pinholes and uneven wetting on the substrate surface, especially on porous or low surface energy paper substrates. Pinholes not only affect the uniformity of the coating's appearance and optical properties, but also weaken its adhesion to the substrate, causing localized coating peeling or incomplete transfer during subsequent processes. In severe cases, it can even result in blurred pattern edges and obvious jagged edges, making it impossible to achieve the process requirements of high-precision local printing.
[0004] Meanwhile, the rheological control of water-based coatings is more complex than that of solvent-based systems. Their rheological parameters, such as viscosity and thixotropy, are significantly affected by the resin system, additive compatibility, and ambient temperature and humidity. Improper control can easily lead to uneven coating, poor leveling, or edge bleeding. In partial printing transfer processes, precise control of the coating's rheological behavior is required to ensure clear pattern edges and consistent film thickness. This places extremely high demands on the formulation design and process control of water-based coatings, as traditional water-based systems often struggle to balance environmental friendliness, drying properties, film-forming properties, and printability. Summary of the Invention
[0005] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a water-based environmentally friendly coating and its local printing transfer paper, which solves the problems that the drying speed of traditional water-based environmentally friendly coatings is much lower than that of solvent-based coatings, that water surface tension causes pinholes and transfer to the substrate, and that local printing coatings are complicated to control due to the rheological properties of water-based coatings.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A water-based environmentally friendly coating and its local printing transfer paper, comprising the following components by weight: 60-80 parts by weight of aqueous epoxy ester dispersion, 10-20 parts by weight of silicone-modified polyvinyl butyral emulsion, 3-8 parts by weight of fumed alumina nano-dispersion, 0.5-2 parts by weight of fluorocarbon surfactant, 1-3 parts by weight of self-crosslinking polyether thickener, and 5-10 parts by weight of propylene glycol methyl ether acetate azeotropic system with water.
[0007] Preferably, the aqueous epoxy ester dispersion includes a dispersion in which polyethylene glycol segments are introduced after esterification of soybean oleic acid with bisphenol A type epoxy resin, and an aqueous dispersion of epoxy soybean oleate grafted with glycidyl methacrylate.
[0008] Preferably, the organosilicon-modified polyvinyl butyral emulsion is a copolymer emulsion in which polydimethylsiloxane segments are grafted onto polyvinyl butyral chains.
[0009] Preferably, the gas-phase alumina nano-dispersion is nano-sized α-alumina produced by the gas-phase method.
[0010] Preferably, the self-crosslinking polyether thickener is a mixture of a hydrophobically modified ethylene oxide polyurethane block polymer and a fluorocarbon surfactant, which is an ethoxylated derivative of a fluorocarbon chain and a carbon-linked chain, in a mass ratio of 3:1.
[0011] A water-based environmentally friendly coating for spot printing transfer paper includes transfer base paper, coating liquid, transfer adhesive layer, and water-based wax layer.
[0012] Preferably, the water-based environmentally friendly coating for partial printing transfer paper is composed of a coating liquid, a transfer adhesive layer, a water-based wax layer, and a transfer base paper stacked in sequence.
[0013] Preferably, the transfer base paper is a glassine release paper with a surface activated by plasma and a basis weight of 80~120g / ㎡, with a surface tension of not less than 42mN / m and an activation layer thickness of 0.1~0.3μm.
[0014] Preferably, the transfer adhesive layer is a composite adhesive layer made of waterborne polyurethane acrylate copolymer emulsion and nano-silica.
[0015] Preferably, the water-based wax layer is a blended emulsion of oxidized polyethylene wax and paraffin wax with a melting point of 50~60℃, wherein the oxidized polyethylene wax accounts for 60%~80%.
[0016] The technical effects and advantages of the water-based environmentally friendly coating and its local printing transfer paper of this invention are as follows: 1. This invention uses propylene glycol methyl ether acetate-water azeotropic drying aid and fluorocarbon surfactant to synergistically reduce tension, combined with 50℃ infrared pre-drying + 110℃ gradient hot air, shortening the surface drying time from the traditional 60 s to 8 s, achieving rapid drying without bubbling or shrinkage.
[0017] 2. In this invention, gas-phase nano-α-Al2O3 pretreated with 30kHz ultrasound completely deagglomerates under high-speed shearing at 1500 rpm, filling the micropores on the paper surface and reducing the pore density of the coating to 0 pores / cm².
[0018] 3. In this invention, the laser-engraved gravure roller precisely limits the wet film to the pattern area of 8~12μm, and then transfers it through non-contact scanning with a 1064 nm infrared laser. The edge serration width is only 5μm, which meets the stringent precision of micron-level local printing.
[0019] 4. In this invention, soybean oil acid-bisphenol A-polyethylene glycol segment waterborne epoxy ester and organosilicon modified PVB interpenetrate crosslink, achieving a hardness of 3H. At the same time, infrared laser-induced interface desorption results in a pattern with sharp edges, no stringing, and no residue after transfer.
[0020] 5. This invention features a fully water-based formula that eliminates slow-drying solvents, resulting in VOC residues of ≤5 ppm. It is safe for direct contact with cigarette packs, food packaging, and children's books, ensuring environmental protection and safety.
[0021] 6. This invention uses a self-crosslinking polyether thickener to precisely lock the viscosity at 25℃ to 800~1500 mPa·s, which ensures leveling and screen hanging under gravure printing, while avoiding excessive thinning and bleeding, and excessive thickening and cracking. It has a wide process window and allows for quick on-site debugging.
[0022] 7. With this invention, the base paper only needs to be corona treated to ≥42 mN / m before it can be directly coated, eliminating the need for pre-coating, priming or base adhesive processes. A single unit can complete coating-drying-transfer, shortening the production line by 30% and reducing energy consumption and labor simultaneously. Attached Figure Description
[0023] Figure 1 This is a flowchart of a water-based environmentally friendly coating and its local printing transfer paper proposed in this invention. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0025] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0026] Example 1 This embodiment provides a water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: 80 parts of aqueous epoxy ester dispersion (a dispersion obtained by esterification of soybean oil acid and bisphenol A type epoxy resin followed by the introduction of polyethylene glycol segments for aqueous treatment), 20 parts of organosilicon-modified polyvinyl butyral emulsion (an aqueous emulsion formed by grafting polydimethylsiloxane segments onto the branches of polyvinyl butyral), 8 parts of fumed alumina nano-dispersion (nano-scale α-alumina produced by fumed process), 2 parts of fluorocarbon surfactant (ethoxylated derivatives of fluorocarbon chain: carbon-linked chain = 3:1), 3 parts of self-crosslinking polyether thickener (hydrophobically modified ethylene oxide polyurethane block polymer), and 10 parts of fast-drying agent (propylene glycol methyl ether acetate and water azeotropic system).
[0027] Experimental objective: A water-based environmentally friendly coating and its local printing transfer paper were prepared.
[0028] Experimental steps: S1: Weigh the aqueous epoxy ester dispersion and the organosilicon-modified polyvinyl butyral emulsion, and stir and preheat them at 25°C and 200 rpm. Simultaneously, sonicate the gas phase alumina nano-dispersion at 30 kHz for 15 minutes, and premix the fluorocarbon surfactant and fast-drying agent evenly for later use. S2: Place the preheated aqueous epoxy ester dispersion in a high-speed disperser, slowly add the organosilicon-modified PVB emulsion at 400 rpm, and continue stirring for 15 minutes until the system is uniform to obtain a milky white blended emulsion. S3: While stirring, slowly add the pretreated alumina nano-dispersion to the white blended emulsion, and increase the speed to 1500 rpm, disperse for 20 minutes until the system is homogeneous and there are no visible particles; S4: Slowly add the premixed fluorocarbon surfactant and quick-drying agent dropwise into the system, and stir at 1000 rpm for 20 minutes; S5: Use a self-crosslinking polyether thickener, add it gradually and control the speed at 300 rpm, monitor the viscosity change in real time, adjust the viscosity to 1500 mPa·s at 25℃, stir and let it stand for 30 minutes to mature. S6: The transfer base paper is corona treated to make its surface tension ≥42 mN / m, and coated with a 5μm thick emulsion of oxidized polyethylene wax and paraffin wax. After pre-baking at 50℃ for 10 seconds, a release interface is formed. Then, a 8μm thick water-based polyurethane acrylate copolymer emulsion and nano silica composite adhesive is coated on the water-based wax layer and pre-baked at 60℃ for 15 seconds. Finally, the cured water-based environmentally friendly coating liquid is precisely coated on the pattern area of the transfer adhesive layer using a laser engraving gravure roller, with the thickness controlled at 12μm. S7: The coated multilayer paper base is first pre-baked at 50℃ for 10 seconds to make the coating surface dry and initially cross-linked. Then it enters the gradient hot air drying zone and is dried at 100℃ for 30 seconds to make the transfer adhesive layer thermally cross-linked to form a microporous structure and complete the gradient curing of the coating from the surface to the inside. S8: The dried multilayer transfer paper is bonded to the substrate, and the coating area is scanned non-contactly according to the pattern using an infrared laser. The laser heat melts the water-based wax layer, and the coating is smoothly detached from the wax layer interface under the adhesion control of the transfer adhesive layer and completely transferred to the substrate, forming a local printing effect with an edge clarity of ≤5μm.
[0029] Experimental results: See Table 1 for details.
[0030] Table 1: Test Results of Example 1
[0031] Example 1 uses an aqueous epoxy ester dispersion that is esterified with soybean oil acid and bisphenol A type epoxy resin and then introduced with polyethylene glycol segments. Combined with optimized ultrasonic treatment and high-speed dispersion process, the nano alumina is fully dispersed and the system has good uniformity. The synergistic effect of fast-drying agent and fluorocarbon surfactant reduces surface tension. With appropriate viscosity control, the coating achieves the best comprehensive performance with fast drying, no shrinkage crater, clear edges, high hardness and extremely low VOC residue.
[0032] Example 2 This embodiment provides a water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: 80 parts of aqueous epoxy ester dispersion (aqueous dispersion of epoxy soybean oleate grafted with glycidyl methacrylate), 20 parts of organosilicon-modified polyvinyl butyral emulsion (aqueous emulsion formed by grafting polydimethylsiloxane segments onto the branches of polyvinyl butyral), 8 parts of fumed alumina nano-dispersion (nano-alumina produced by fumed process), 2 parts of fluorocarbon surfactant (ethoxylated derivatives of fluorocarbon chain: carbon linkage chain = 3:1), 3 parts of self-crosslinking polyether thickener (hydrophobic modified ethylene oxide polyurethane block polymer), and 10 parts of fast-drying agent (azeotropic system of propylene glycol methyl ether acetate and water).
[0033] Experimental objective: The aqueous epoxy ester dispersion was replaced with an aqueous dispersion of epoxy soybean oleate grafted with glycidyl methacrylate.
[0034] Experimental steps: S1: Weigh the aqueous epoxy ester dispersion and the organosilicon-modified polyvinyl butyral emulsion, and stir and preheat them at 25°C and 200 rpm. Simultaneously, sonicate the gas phase alumina nano-dispersion at 30 kHz for 15 minutes, and premix the fluorocarbon surfactant and fast-drying agent evenly for later use. S2: Place the preheated aqueous epoxy ester dispersion in a high-speed disperser, slowly add the organosilicon-modified PVB emulsion at 400 rpm, and continue stirring for 15 minutes until the system is uniform to obtain a milky white blended emulsion. S3: While stirring, slowly add the pretreated alumina nano-dispersion to the white blended emulsion, and increase the speed to 1500 rpm, disperse for 20 minutes until the system is homogeneous and there are no visible particles; S4: Slowly add the premixed fluorocarbon surfactant and quick-drying agent dropwise into the system, and stir at 1000 rpm for 20 minutes; S5: Use a self-crosslinking polyether thickener, add it gradually and control the speed at 300 rpm, monitor the viscosity change in real time, adjust the viscosity to 1500 mPa·s at 25℃, stir and let it stand for 30 minutes to mature. S6: The transfer base paper is corona treated to make its surface tension ≥42 mN / m, and coated with a 5μm thick emulsion of oxidized polyethylene wax and paraffin wax. After pre-baking at 50℃ for 10 seconds, a release interface is formed. Then, a 8μm thick water-based polyurethane acrylate copolymer emulsion and nano silica composite adhesive is coated on the water-based wax layer and pre-baked at 60℃ for 15 seconds. Finally, the cured water-based environmentally friendly coating liquid is precisely coated on the pattern area of the transfer adhesive layer using a laser engraving gravure roller, with the thickness controlled at 12μm. S7: The coated multilayer paper base is first pre-baked at 50℃ for 10 seconds to make the coating surface dry and initially cross-linked. Then it enters the gradient hot air drying zone and is dried at 100℃ for 30 seconds to make the transfer adhesive layer thermally cross-linked to form a microporous structure and complete the gradient curing of the coating from the surface to the inside. S8: The dried multilayer transfer paper is bonded to the substrate, and the coating area is scanned non-contactly according to the pattern using an infrared laser. The laser heat melts the water-based wax layer, and the coating is smoothly detached from the wax layer interface under the adhesion control of the transfer adhesive layer and completely transferred to the substrate, forming a local printing effect with an edge clarity of ≤5μm.
[0035] Experimental results: See Table 2 for details.
[0036] Table 2: Test Results of Example 2
[0037] Example 2 uses an epoxy soybean oleate dispersion grafted with glycidyl methylpropionate to modify the aqueous epoxy ester dispersion. Its molecular structure has weak hydrophilicity and slow curing and crosslinking speed, which leads to prolonged drying time, decreased surface wettability, the appearance of pinholes and edge serrations, reduced hardness, and increased VOC residue.
[0038] Example 3 This embodiment provides a water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: 80 parts of aqueous epoxy ester dispersion (a dispersion obtained by esterification of soybean oil acid and bisphenol A type epoxy resin followed by the introduction of polyethylene glycol segments for aqueous treatment), 20 parts of organosilicon-modified polyvinyl butyral emulsion (an aqueous emulsion formed by grafting polydimethylsiloxane segments onto the branches of polyvinyl butyral), 8 parts of fumed alumina nano-dispersion (nano-scale α-alumina produced by fumed process), 2 parts of fluorocarbon surfactant (ethoxylated derivatives of fluorocarbon chain: carbon-linked chain = 3:1), 3 parts of self-crosslinking polyether thickener (hydrophobically modified ethylene oxide polyurethane block polymer), and 10 parts of fast-drying agent (propylene glycol methyl ether acetate and water azeotropic system).
[0039] Experimental objective: The frequency and treatment time of ultrasonic treatment of gas-phase alumina nano-dispersion in S1 were changed.
[0040] Experimental steps: S1: Weigh the aqueous epoxy ester dispersion and the organosilicon-modified polyvinyl butyral emulsion, and stir and preheat them at 25°C and 200 rpm. Simultaneously, sonicate the gas phase alumina nano-dispersion at 20 kHz for 10 minutes, and premix the fluorocarbon surfactant and fast-drying agent evenly for later use. S2: Place the preheated aqueous epoxy ester dispersion in a high-speed disperser, slowly add the organosilicon-modified PVB emulsion at 400 rpm, and continue stirring for 15 minutes until the system is uniform to obtain a milky white blended emulsion. S3: While stirring, slowly add the pretreated alumina nano-dispersion to the white blended emulsion, and increase the speed to 1500 rpm, disperse for 20 minutes until the system is homogeneous and there are no visible particles; S4: Slowly add the premixed fluorocarbon surfactant and quick-drying agent dropwise into the system, and stir at 1000 rpm for 20 minutes; S5: Use a self-crosslinking polyether thickener, add it gradually and control the speed at 300 rpm, monitor the viscosity change in real time, adjust the viscosity to 1500 mPa·s at 25℃, stir and let it stand for 30 minutes to mature. S6: The transfer base paper is corona treated to make its surface tension ≥42 mN / m, and coated with a 5μm thick emulsion of oxidized polyethylene wax and paraffin wax. After pre-baking at 50℃ for 10 seconds, a release interface is formed. Then, a 8μm thick water-based polyurethane acrylate copolymer emulsion and nano silica composite adhesive is coated on the water-based wax layer and pre-baked at 60℃ for 15 seconds. Finally, the cured water-based environmentally friendly coating liquid is precisely coated on the pattern area of the transfer adhesive layer using a laser engraving gravure roller, with the thickness controlled at 12μm. S7: The coated multilayer paper base is first pre-baked at 50℃ for 10 seconds to make the coating surface dry and initially cross-linked. Then it enters the gradient hot air drying zone and is dried at 100℃ for 30 seconds to make the transfer adhesive layer thermally cross-linked to form a microporous structure and complete the gradient curing of the coating from the surface to the inside. S8: The dried multilayer transfer paper is bonded to the substrate, and the coating area is scanned non-contactly according to the pattern using an infrared laser. The laser heat melts the water-based wax layer, and the coating is smoothly detached from the wax layer interface under the adhesion control of the transfer adhesive layer and completely transferred to the substrate, forming a local printing effect with an edge clarity of ≤5μm.
[0041] Experimental results: See Table 3 for details.
[0042] Table 3: Test Results of Example 3
[0043] Example 3 reduced the ultrasonic treatment intensity of the alumina nano-dispersion, resulting in insufficient dispersion of nanoparticles, decreased system uniformity, and affected coating density and surface smoothness. Although the drying time and hardness were acceptable, a small number of shrinkage cavities and edge jaggedness still appeared, and the VOC residue was slightly higher than in Example 1.
[0044] Example 4 This embodiment provides a water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: 80 parts of aqueous epoxy ester dispersion (a dispersion obtained by esterification of soybean oil acid and bisphenol A type epoxy resin followed by the introduction of polyethylene glycol segments for aqueous treatment), 20 parts of organosilicon-modified polyvinyl butyral emulsion (an aqueous emulsion formed by grafting polydimethylsiloxane segments onto the branches of polyvinyl butyral), 8 parts of fumed alumina nano-dispersion (nano-scale α-alumina produced by fumed process), 2 parts of fluorocarbon surfactant (ethoxylated derivatives of fluorocarbon chain: carbon-linked chain = 3:1), 3 parts of self-crosslinking polyether thickener (hydrophobically modified ethylene oxide polyurethane block polymer), and 10 parts of fast-drying agent (propylene glycol methyl ether acetate and water azeotropic system).
[0045] Experimental objective: Reduce the stirring speed after adding the pretreated alumina nano-dispersion to S3.
[0046] Experimental steps: S1: Weigh the aqueous epoxy ester dispersion and the organosilicon-modified polyvinyl butyral emulsion, and stir and preheat them at 25°C and 200 rpm. Simultaneously, sonicate the gas phase alumina nano-dispersion at 30 kHz for 15 minutes, and premix the fluorocarbon surfactant and fast-drying agent evenly for later use. S2: Place the preheated aqueous epoxy ester dispersion in a high-speed disperser, slowly add the organosilicon-modified PVB emulsion at 400 rpm, and continue stirring for 15 minutes until the system is uniform to obtain a milky white blended emulsion. S3: While stirring, slowly add the pretreated alumina nano-dispersion to the white blended emulsion, and increase the speed to 1200 rpm, disperse for 20 minutes until the system is homogeneous and there are no visible particles; S4: Slowly add the premixed fluorocarbon surfactant and quick-drying agent dropwise into the system, and stir at 1000 rpm for 20 minutes; S5: Use a self-crosslinking polyether thickener, add it gradually and control the speed at 300 rpm, monitor the viscosity change in real time, adjust the viscosity to 1500 mPa·s at 25℃, stir and let it stand for 30 minutes to mature. S6: The transfer base paper is corona treated to make its surface tension ≥42 mN / m, and coated with a 5μm thick emulsion of oxidized polyethylene wax and paraffin wax. After pre-baking at 50℃ for 10 seconds, a release interface is formed. Then, a 8μm thick water-based polyurethane acrylate copolymer emulsion and nano silica composite adhesive is coated on the water-based wax layer and pre-baked at 60℃ for 15 seconds. Finally, the cured water-based environmentally friendly coating liquid is precisely coated on the pattern area of the transfer adhesive layer using a laser engraving gravure roller, with the thickness controlled at 12μm. S7: The coated multilayer paper base is first pre-baked at 50℃ for 10 seconds to make the coating surface dry and initially cross-linked. Then it enters the gradient hot air drying zone and is dried at 100℃ for 30 seconds to make the transfer adhesive layer thermally cross-linked to form a microporous structure and complete the gradient curing of the coating from the surface to the inside. S8: The dried multilayer transfer paper is bonded to the substrate, and the coating area is scanned non-contactly according to the pattern using an infrared laser. The laser heat melts the water-based wax layer, and the coating is smoothly detached from the wax layer interface under the adhesion control of the transfer adhesive layer and completely transferred to the substrate, forming a local printing effect with an edge clarity of ≤5μm.
[0047] Experimental results: See Table 4 for details.
[0048] Table 4: Test Results of Example 4
[0049] In Example 4, the stirring speed was reduced after adding alumina nano-dispersion, resulting in uneven dispersion of nanoparticles in the system. Partial agglomeration led to uneven internal structure of the coating, affecting surface quality and transfer accuracy. This manifested as slower drying, increased pinholes, enlarged edge serrations, decreased hardness, and VOC residue increased to 15 ppm.
[0050] Example 5 This embodiment provides a water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: 80 parts of aqueous epoxy ester dispersion (a dispersion obtained by esterification of soybean oil acid and bisphenol A type epoxy resin followed by the introduction of polyethylene glycol segments for aqueous treatment), 20 parts of organosilicon-modified polyvinyl butyral emulsion (an aqueous emulsion formed by grafting polydimethylsiloxane segments onto the branches of polyvinyl butyral), 8 parts of fumed alumina nano-dispersion (nano-scale α-alumina produced by fumed process), 2 parts of fluorocarbon surfactant (ethoxylated derivatives of fluorocarbon chain: carbon-linked chain = 3:1), 3 parts of self-crosslinking polyether thickener (hydrophobically modified ethylene oxide polyurethane block polymer), and 10 parts of fast-drying agent (propylene glycol methyl ether acetate and water azeotropic system).
[0051] Experimental objective: The viscosity of the system after adding the self-crosslinking polyether thickener in S5 was changed.
[0052] Experimental steps: S1: Weigh the aqueous epoxy ester dispersion and the organosilicon-modified polyvinyl butyral emulsion, and stir and preheat them at 25°C and 200 rpm. Simultaneously, sonicate the gas phase alumina nano-dispersion at 30 kHz for 15 minutes, and premix the fluorocarbon surfactant and fast-drying agent evenly for later use. S2: Place the preheated aqueous epoxy ester dispersion in a high-speed disperser, slowly add the organosilicon-modified PVB emulsion at 400 rpm, and continue stirring for 15 minutes until the system is uniform to obtain a milky white blended emulsion. S3: While stirring, slowly add the pretreated alumina nano-dispersion to the white blended emulsion, and increase the speed to 1500 rpm, disperse for 20 minutes until the system is homogeneous and there are no visible particles; S4: Slowly add the premixed fluorocarbon surfactant and quick-drying agent dropwise into the system, and stir at 1000 rpm for 20 minutes; S5: Use a self-crosslinking polyether thickener, add it gradually and control the speed at 300 rpm, monitor the viscosity change in real time, adjust the viscosity to 800 mPa·s at 25℃, stir and let it stand for 30 minutes to mature. S6: The transfer base paper is corona treated to make its surface tension ≥42 mN / m, and coated with a 5μm thick emulsion of oxidized polyethylene wax and paraffin wax. After pre-baking at 50℃ for 10 seconds, a release interface is formed. Then, a 8μm thick water-based polyurethane acrylate copolymer emulsion and nano silica composite adhesive is coated on the water-based wax layer and pre-baked at 60℃ for 15 seconds. Finally, the cured water-based environmentally friendly coating liquid is precisely coated on the pattern area of the transfer adhesive layer using a laser engraving gravure roller, with the thickness controlled at 12μm. S7: The coated multilayer paper base is first pre-baked at 50℃ for 10 seconds to make the coating surface dry and initially cross-linked. Then it enters the gradient hot air drying zone and is dried at 100℃ for 30 seconds to make the transfer adhesive layer thermally cross-linked to form a microporous structure and complete the gradient curing of the coating from the surface to the inside. S8: The dried multilayer transfer paper is bonded to the substrate, and the coating area is scanned non-contactly according to the pattern using an infrared laser. The laser heat melts the water-based wax layer, and the coating is smoothly detached from the wax layer interface under the adhesion control of the transfer adhesive layer and completely transferred to the substrate, forming a local printing effect with an edge clarity of ≤5μm.
[0053] Experimental results: See Table 5 for details.
[0054] Table 5: Test Results of Example 5
[0055] Example 5 controlled the final viscosity at 800 mPa·s by adjusting the amount of thickener added, making the coating rheology more suitable for gravure printing, and improving coating uniformity and drying efficiency. Therefore, the drying time is shorter, there are fewer pinholes, the edges are clearer, the hardness is maintained at 3H, and the VOC residue is only 8 ppm, with performance close to that of Example 1.
[0056] Example 6 This embodiment provides a water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: 80 parts of aqueous epoxy ester dispersion (a dispersion obtained by esterification of soybean oil acid and bisphenol A type epoxy resin followed by the introduction of polyethylene glycol segments for aqueous treatment), 20 parts of organosilicon-modified polyvinyl butyral emulsion (an aqueous emulsion formed by grafting polydimethylsiloxane segments onto the branches of polyvinyl butyral), 8 parts of fumed alumina nano-dispersion (nano-scale α-alumina produced by fumed process), 2 parts of fluorocarbon surfactant (ethoxylated derivatives of fluorocarbon chain: carbon-linked chain = 3:1), 3 parts of self-crosslinking polyether thickener (hydrophobically modified ethylene oxide polyurethane block polymer), and 10 parts of fast-drying agent (propylene glycol methyl ether acetate and water azeotropic system).
[0057] Experimental objective: Change the coating thickness in S6.
[0058] Experimental steps: S1: Weigh the aqueous epoxy ester dispersion and the organosilicon-modified polyvinyl butyral emulsion, and stir and preheat them at 25°C and 200 rpm. Simultaneously, sonicate the gas phase alumina nano-dispersion at 30 kHz for 15 minutes, and premix the fluorocarbon surfactant and fast-drying agent evenly for later use. S2: Place the preheated aqueous epoxy ester dispersion in a high-speed disperser, slowly add the organosilicon-modified PVB emulsion at 400 rpm, and continue stirring for 15 minutes until the system is uniform to obtain a milky white blended emulsion. S3: While stirring, slowly add the pretreated alumina nano-dispersion to the white blended emulsion, and increase the speed to 1500 rpm, disperse for 20 minutes until the system is homogeneous and there are no visible particles; S4: Slowly add the premixed fluorocarbon surfactant and quick-drying agent dropwise into the system, and stir at 1000 rpm for 20 minutes; S5: Use a self-crosslinking polyether thickener, add it gradually and control the speed at 300 rpm, monitor the viscosity change in real time, adjust the viscosity to 1500 mPa·s at 25℃, stir and let it stand for 30 minutes to mature. S6: The transfer base paper is corona treated to make its surface tension ≥42 mN / m, and coated with a 5μm thick emulsion of oxidized polyethylene wax and paraffin wax. After pre-baking at 50℃ for 10 seconds, a release interface is formed. Then, a 8μm thick water-based polyurethane acrylate copolymer emulsion and nano silica composite adhesive is coated on the water-based wax layer and pre-baked at 60℃ for 15 seconds. Finally, the cured water-based environmentally friendly coating liquid is precisely coated on the pattern area of the transfer adhesive layer using a laser engraving gravure roller, with the thickness controlled at 8μm. S7: The coated multilayer paper base is first pre-baked at 50℃ for 10 seconds to make the coating surface dry and initially cross-linked. Then it enters the gradient hot air drying zone and is dried at 100℃ for 30 seconds to make the transfer adhesive layer thermally cross-linked to form a microporous structure and complete the gradient curing of the coating from the surface to the inside. S8: The dried multilayer transfer paper is bonded to the substrate, and the coating area is scanned non-contactly according to the pattern using an infrared laser. The laser heat melts the water-based wax layer, and the coating is smoothly detached from the wax layer interface under the adhesion control of the transfer adhesive layer and completely transferred to the substrate, forming a local printing effect with an edge clarity of ≤5μm.
[0059] Experimental results: See Table 6 for details.
[0060] Table 6: Test Results of Example 6
[0061] Example 6 reduced the wet film thickness to 8 μm. The coating was too thin, which led to a decrease in mechanical strength and incomplete surface coverage. Defects were easily generated during drying and transfer, such as increased pinholes, enlarged edge serrations, and reduced hardness. The drying time was slightly longer, and the VOC residue was 12 ppm. This indicates that the coating thickness needs to be controlled within an appropriate range to ensure performance.
[0062] Comparative Example 1 This embodiment provides a traditional water-based environmentally friendly coating and its local printing transfer paper, and the specific implementation steps include: Experimental materials: The mixture consists of 85 parts of waterborne acrylic emulsion, 10 parts of industrial ethanol, 5 parts of deionized water, 2 parts of polyvinyl butyral powder, 2 parts of propylene glycol butyl ether slow-drying solvent, 0.5 parts of cross-linked acrylic-acrylate copolymer emulsion, 3 parts of hexamethoxymethyl melamine, and 0.3 parts of polyether-modified polysiloxane.
[0063] Experimental objective: The differences between traditional water-based formulations and the embodiments of the present invention in terms of drying speed, pore suppression, transfer accuracy, and VOC residue were verified as a comparative benchmark.
[0064] Experimental steps: S1: Add aqueous acrylic emulsion, deionized water, ethanol, and wetting agent to a mixing tank and mix at 200 rpm at room temperature for 10 min; S2: Slowly add PVB powder and disperse at 600 rpm for 20 min until no particles remain; S3: Add amino resin crosslinking agent and stir at 400 rpm for 5 min; S4: Add alkali-swelling thickener dropwise to adjust the viscosity to 1200 mPa·s at 25 ℃; S5: Finally, add PnB slow-drying solvent, stir at 200 rpm for 5 min, and let stand to defoam before use; S6: Corona treatment of the transfer base paper (surface tension 38 mN / m), full-surface coating with a 120-line gravure roller, wet film thickness 12 μm; S7: Dry with hot air at 50 ℃ for 60 s, then cure at 90 ℃ for 120 s; S8: Lay the coated paper onto the PET substrate and use a 1064 nm infrared laser to scan the entire area (power 18 W, speed 100 mm / s) to transfer the coating throughout.
[0065] Experimental results: See Table 7 for details.
[0066] Table 7: Test Results of Comparative Example 1
[0067] Comparative Example 1 uses a traditional water-based acrylic system without any special fast-drying additives or nano-reinforcing phases. It relies on slow-drying solvents and physical mixing processes, resulting in extremely slow drying, numerous pinholes, severe edge jaggedness, a hardness of only HB grade, and VOC residue as high as 45ppm. Neither the formulation design nor the process was optimized for local printing transfer, highlighting the significant advantages of this invention in terms of drying speed, surface quality, and environmental friendliness.
[0068] refer to Figure 1 The flowchart of Example 1 shows that an aqueous epoxy ester dispersion made by esterifying soybean oil acid and bisphenol A type epoxy resin and then introducing hydrophilic polyethylene glycol segments is used as the main film-forming substance. Combined with a gas-phase alumina nano-dispersion pretreatment process of ultrasonic treatment at 30 kHz for 15 minutes and a high-speed dispersion process at 1500 rpm, a highly uniform dispersion of nanoparticles and system stability are achieved.
[0069] Example 2 uses an aqueous dispersion of glycidyl methacrylate grafted with glycidyl methacrylate as the main resin base. Although this structure has a certain modification effect, its hydrophilic segment design and curing activity are different from those of the system used in Example 1, resulting in a decrease in its drying performance, surface wettability and the overall performance of the final coating under the same process conditions.
[0070] In Example 3, while maintaining the same main formulation as in Example 1, the pretreatment parameters of the gas-phase alumina nano-dispersion were adjusted. The ultrasonic treatment conditions were reduced to 20 kHz for 10 minutes. This reduced dispersion energy input resulted in insufficient deagglomeration and dispersion uniformity of the nano-alumina particles in the system, which in turn affected the density and surface smoothness of the coating.
[0071] In Example 4, the stirring speed was adjusted from 1500 rpm to 1200 rpm during the nanoparticle addition stage. Although this was still within the process range, the reduction in shear force resulted in a loss of uniformity in the dispersion of nano-alumina in the emulsion. The agglomeration of some particles led to microscopic inhomogeneity in the internal structure of the coating, which in turn had an observable negative impact on surface quality and mechanical properties.
[0072] Example 5: By adjusting the amount of self-crosslinking polyether thickener added, the final viscosity of the coating system at 25°C was precisely controlled at 800 mPa·s, making its rheological properties more in line with the process requirements of gravure printing, thereby forming a more uniform wet film during the coating process, which is beneficial to the improvement of drying efficiency and surface morphology.
[0073] In Example 6, the wet film coating thickness was adjusted from 12 μm to 8 μm. The thinner coating is more prone to localized insufficient coverage and reduced strength during the drying and curing process, resulting in a certain degree of attenuation in edge integrity, mechanical support and defect control during the transfer printing process.
[0074] Comparative Example 1 uses traditional aqueous acrylic emulsion as the main film-forming substance, combined with industrial ethanol, slow-drying solvent propylene glycol butyl ether, and physically blended polyvinyl butyral powder. Its formulation does not introduce nano-reinforcing materials and structured fast-drying agents, and its process also lacks systematic optimization for nano-dispersion and gradient drying. Therefore, it is significantly inferior to the embodiments of the present invention in terms of drying rate, surface defect control, edge precision, and environmental friendliness.
[0075] Comparing the examples and comparative examples, Example 1 achieves the optimal balance between drying speed, surface quality, hardness, and environmental friendliness. It cleverly enhances the overall performance of the coating through the synergistic effect of the waterborne epoxy ester structure and the efficient dispersion of nano-alumina, making it suitable for high-precision, environmentally friendly local printing transfer applications. Example 2, while experimenting with different epoxy ester structures, suffers from insufficient hydrophilicity and curing efficiency, leading to a decline in overall performance. Example 3 employs insufficient ultrasonic dispersion conditions, failing to fully deagglomerate the nanoparticles and affecting coating density. Example 4 uses a lower stirring speed, resulting in uneven nanoparticle dispersion and poor coating uniformity. Example 5 uses a lower final viscosity, but improves coating rheology, achieving near-optimal performance. Example 6 uses a thinner coating thickness, but results in insufficient coating strength and coverage, affecting usability. The comparative examples highlight the limitations of traditional waterborne coatings in terms of fast drying, surface defect control, and VOC emissions. Therefore, this invention effectively solves the key technical challenges faced by waterborne coatings in local printing transfer through specific component design, process parameters, and structural control.
[0076] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of protection of the claims.
[0077] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A water-based environmentally friendly coating, characterized in that, The product is composed of the following components by weight: 60-80 parts by weight of aqueous epoxy ester dispersion, 10-20 parts by weight of silicone-modified polyvinyl butyral emulsion, 3-8 parts by weight of fumed alumina nano-dispersion, 0.5-2 parts by weight of fluorocarbon surfactant, 1-3 parts by weight of self-crosslinking polyether thickener, and 5-10 parts by weight of propylene glycol methyl ether acetate azeotropic system with water.
2. The water-based environmentally friendly coating as described in claim 1, characterized in that, Aqueous epoxy ester dispersions include dispersions in which polyethylene glycol segments are introduced after esterification of soybean oleic acid with bisphenol A type epoxy resin, and aqueous dispersions of epoxy soybean oleate grafted with glycidyl methacrylate.
3. The water-based environmentally friendly coating as described in claim 1, characterized in that, The organosilicon-modified polyvinyl butyral emulsion is a copolymer emulsion in which polydimethylsiloxane segments are grafted onto polyvinyl butyral chains.
4. The water-based environmentally friendly coating as described in claim 1, characterized in that, The gas-phase alumina nano-dispersion is nano-sized α-alumina produced by the gas-phase method.
5. The water-based environmentally friendly coating as described in claim 1, characterized in that, The self-crosslinking polyether thickener is a mixture of hydrophobically modified ethylene oxide polyurethane block polymer and fluorocarbon surfactant, which are ethoxylated derivatives of fluorocarbon chains and carbon linkage chains, in a mass ratio of 3:
1.
6. A water-based environmentally friendly coated spot printing transfer paper, characterized in that, It includes transfer base paper, coating liquid as described in any one of claims 1 to 5, transfer adhesive layer, and water-based wax layer.
7. The water-based environmentally friendly coating for partial printing transfer paper as described in claim 6, characterized in that, The water-based environmentally friendly coating for partial printing transfer paper is composed of coating liquid, transfer adhesive layer, water-based wax layer, and transfer base paper stacked in sequence.
8. The water-based environmentally friendly coating for partial printing transfer paper as described in claim 6, characterized in that, The transfer base paper is a glassine release paper with a basis weight of 80~120g / ㎡ that has undergone plasma activation treatment, with a surface tension of not less than 42mN / m and an activation layer thickness of 0.1~0.3μm.
9. The water-based environmentally friendly coating for partial printing transfer paper as described in claim 6, characterized in that, The transfer adhesive layer is a composite adhesive layer made of waterborne polyurethane acrylate copolymer emulsion and nano-silica.
10. The water-based environmentally friendly coating for partial printing transfer paper as described in claim 6, characterized in that, The water-based wax layer is a blend emulsion of oxidized polyethylene wax and paraffin wax with a melting point of 50~60℃, wherein the oxidized polyethylene wax accounts for 60%~80%.
Citation Information
Patent Citations
Organosilicon-modified polyvinyl butyral coil coating
CN101824254A
Aqueous epoxy resin emulsion synthesized with mono-isocyanate polyoxyethylene monomethyl ether monomers
CN107189037A
Waterborne epoxy ester dispersion as well as preparation method and application thereof
CN112679682A
Pyrography transfer paper and application thereof
CN113135055A
Quick-drying corrosion-resistant waterborne epoxy ester coating and preparation method thereof
CN119752271A
Cited By
High-performance paper yarn and preparation method thereof
CN121802598A